The Influence Of Market Orientation And Innovation On Business Performance In MSMEes Through Competitive Advantage - Siti Nuryati; Agtovia Frimayasa; Zaenal Arief (Sean Institute, 2024)
This research aims to analyze the influence of market orientation and innovation on business performance in Micro, Small, and Medium Enterprises (MSMEs) through competitive advantage. Market orientation is a strategic approach prioritizes customer needs and preferences in business activities. On the other hand, innovation is the process of creating and implementing new ideas to create significant value. This study uses a quantitative approach by collecting primary data through questionnaires distributed to MSME owners or managers. The research sample was taken randomly from the MSME population operating in different sectors. Regression analysis examines the relationship between market orientation, innovation, competitive advantage, and business performance. This explanatory research type uses hypothesis testing to explain causal relationships between variables. One hundred respondents from MSMEs were the samples in this research. Using a technique known as non-probability sampling. T and Sobel tests are used to test hypotheses. Partial Least Square (PLS) was used for data analysis, and SmartPLS 3.0 software was used to assist the research. The findings from this research provide an important contribution for MSME owners or managers in understanding the importance of market orientation and innovation as determining factors of competitive advantage and business performance. In increasingly fierce competition, MSMEs must focus on customers, adopt innovative approaches, and utilize competitive advantages to achieve long-term success.